Far-field properties of a vortex airy beam - Chew, Khian Hooi; Chen, R.P. (2013)
Analytical far-field expressions for the transverse electric mode and transverse electric magnetic mode terms, and the energy flux distributions of vortex Airy beams are derived based on the vector angular spectrum of the beam and the stationary phase method. The physical pictures of vortex Airy beams from the vectorial structure are illustrated and the energy flux distributions are demonstrated in far-field. The influences of the beam parameters, especially the exponential factor, on the energy flux distributions of vortex Airy beams and its transverse electric mode and transverse electric magnetic mode terms are discussed. This work provides a new understanding of the propagation behaviors and applications of a vortex Airy beam.